The using of psychodynamic tests in educational processes in preschool institutions - Zokirova Madina; Khudaiberdiyeva Dilafruz Abidovna (Zien Journals, 2022)
This article is aimed at understanding the importance and significance of psychodynamic tests in the study of children's personality in the educational process in preschool education, as well as psychodynamic tests in the field of child development and 5 centers in the "First Step" program about the ways of transmission in connection with
Keywords: pedagogical diagnostics; psychodynamic approach; psychodynamics; test